Applied nanotechnology the conversion of research results to products - Ramsden, Jeremy
An overview of nanotechnology that encompasses scientific, technological, economic and social issues - investigating the potential of nanotechnology to transform whole sectors of industry from healthcare to energy. Jeremy Ramsden provides a blueprint for those involved in the commercialization of nanotechnology. In Applied Nanotechnology Professor Ramsden takes an integrated approach to the scientific, commercial and social aspects of nanotechnology, exploring: The relationship between nanotechnology and innovation The changing economics and business models required to commercialize innovations in nanotechnology Product design challenges - investigated through case studies Applications in various sectors, including composite materials, energy and agriculture The role of government in promoting nanotechnology The potential future of molecular self-assembly in industrial production The ethics and social implications of nanotechnology As well as providing business models and practical examples of the innovation process, this book offers a vision of the role of nanotechnology in confronting the challenges facing humanity, from healthcare to climate change. About the Author Professor Jeremy Ramsden graduated (Natural Sciences) from Cambridge University and obtained his doctorate from the cole Polytechnique Fdrale in Lausanne. He was appointed as Professor of Nanotechnology at Cranfield University in 2002, becoming additionally Director of Research for Bionanotechnology at Cranfield University's Kitakyushu campus in 2003.